Tinjauan Yuridis Terhadap Penerapan Asas Akusator Dalam Hukum Acara Pidana Indonesia - Yulianto, Nanda Dirka (JURNAL PROPERTY RIGHTS, 2014)
Aviolence action by law enforcer apparatus,especially police investigator, physically or psychologically, to ask the suspect admit a mistake that net certain to do in preliminary investigation to get an admission of his / her crime.            Based on that case , this research take problems formula that are , How is the accusatoir basic application in procedure of criminal of Indonesia and what is the law implication as the result of unfulfilled accusatoir basic in procedure of criminal of Indonesia. The objectives of this research are to know and to analyze the law application and law implication of unfulfilled accusatoir basic. The benefits are to give comprehension about the law application and law implication of unfulfilled accusatoir basic.            Kind of research on this research is normative juridical law research using law approach method and conceptual approach method. Kind of law material of this research was got from primes law material, secondary and tertiary law material, and then to be analyzed using inductive deductive analysis technique.            From the result of the method above, this accusatoir basic and already applied on the beginning processof criminal jurisdiction , the law implication of unfulfilled accusatoir basic is a violation of human right that not appropriate with Indonesia philosophy and cause null and void decision for law .